Transformasi Digital sebagai Strategi Keunggulan Kompetitif Rumah Sakit di Era Jaminan Kesehatan Nasional : Tinjauan Literatur - Lydia Gloriani Lethe; Tito Santana; Purwadhi Purwadhi; Yani Restiani Widjaja (Lembaga Pengembangan Kinerja Dosen, 2026)
Digital transformation has become a crucial strategy for hospitals to improve efficiency, service quality, and competitiveness in the era of the National Health Insurance (Jaminan Kesehatan Nasional, JKN). The implementation of the INA-CBGs payment system requires hospitals to manage resources efficiently, making digital technologies a key source of competitive advantage. This study aims to examine the role of digital transformation as a competitive strategy for hospitals within the JKN context through a Systematic Literature Review (SLR). Literature was collected from Scopus, PubMed, Google Scholar, and Sinta databases following the PRISMA 2020 guidelines. Out of 835 identified articles, 38 studies met the inclusion criteria and were analyzed thematically. The findings indicate that digital transformation enhances operational efficiency, service quality, decision-making accuracy, and patient satisfaction. The adoption of hospital information systems, electronic medical records, and telemedicine supports service differentiation and strengthens hospital competitiveness. Successful digital transformation depends on strategic alignment, human resource readiness, leadership commitment, and effective information technology governance. This study concludes that digital transformation is a key managerial strategy for achieving sustainable competitive advantage in hospitals under the JKN system.